PROPHETIC INTELLIGENCE DISCOURSE IN ISLAMIC RELIGIOUS EDUCATION - Suparman, Fatah; Subando, Joko; Abbas, Ngatmin (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to conduct a discourse on intelligence concepts IQ (Intelligence Quotient), EQ (Emotional Quotient), SQ (Spiritual Quotient), and PI (Prophetic Intelligence) and the role of each intelligence in forming a perfect and noble human being. This study uses a qualitative approach with the method of literature study and theoretical analysis. This approach involves searching for and analyzing relevant theoretical sources to gain an in-depth understanding of the research topic. The method of literature study and theoretical analysis is used to describe the concepts that appear in the literature and build a solid conceptual framework. This approach is important in developing quality research and providing a holistic understanding of the topic under study. The results of this study indicate that in the discourse on intelligence, the concepts of IQ (Intelligence Quotient), EQ (Emotional Quotient), SQ (Spiritual Quotient), and PI (Prophetic Intelligence) have differences and their respective roles. IQ is likened to